Genetic basis of immune-mediated susceptibility to infectious disease - Vivek , N (2015)
Infectious diseases remain a major driver of morbidity and mortality globally. For example, Mycobacterium tuberculosis causes about 10 million cases of tuberculosis (TB) and 1.5 million deaths. In a series of studies I demonstrate that discovering the genetic underpinnings of how immune factors affect susceptibility to diseases such as TB reveal new insights into disease susceptibility. Previous transcriptome-wide studies suggested that the ratio of myeloid:lymphoid transcripts was elevated in infants who subsequently developed TB. These data were reminiscent of observations made 80 years ago where the ratio of monocytes:lymphocytes (ML) at time of challenge with mycobacteria, was predictive of survival in animal models. To establish the peripheral blood ML ratio as a novel intermediate phenotype for TB susceptibility, I demonstrated that the ML ratio predicts TB disease in three independent cohorts of adults (n=2207), infants (n=1336) and pregnant women (n=1202). Moreover, in collaboration with others, these findings were extended to other diseases including malaria. Turning attention to the pathophysiologic basis of this association, I found qualitative differences in monocytes according to ML ratio even amongst healthy individuals (n=136), both in functional response to mycobacteria and in transcriptomic profile at rest. Next, I found that the ML and neutrophil:lymphocyte (NL) ratio are highly phenotypically and genetically correlated, suggesting the presence of pleiotropic genetic regulators. I present formal estimates of heritability based on concordance and structural equation modeling of data from twin studies (1664 twin pairs), and amongst unrelated adults (n=5034). A meta-analysis of four genome-wide association studies (total n=5768) was performed as a resource to understand how the ML and NL ratios may be regulated, and to facilitate Mendelian randomization studies. Finally, in a more generalised approach I identified genetic regulators of gene expression in monocytes and neutrophils from healthy adults (n=101) and demonstrated how these give fundamental new insights into a wide array of infectious and non-infectious diseases. Taken together, these studies offer original contributions to the understanding of how genetic factors give rise to immune-mediated susceptibility to infectious disease.